Fiscal competition over taxes and public inputs : theory and evidence - Sebastian Hauptmeier; Ferdinand Mittermaier; Johannes Rincke (Center for Economic Studies and ifo Institute (CESifo), 2009)
We set up a model to characterize the reaction functions of governments competing for mobile capital by simultaneously setting both the business tax rate as well as the level of provision of a productive public input. Using a rich data set of local jurisdictions, we then test the predictions of the model with respect to the nature of strategic interaction among governments. Our findings from efficient estimation of a system of spatially interrelated equations for both policy instruments support the notion that local governments use both the business tax rate and public inputs to compete for capital. In particular, we find that if neighbors cut their tax rates, governments try to restore competitiveness by lowering their own tax and increasing spending on public inputs. If neighbors provide more infrastructure, governments react by increasing their own spending on public inputs.
Keywords: H72; H77; C72; 330; Tax competition; public input; competition; system estimation; Kommunale Wirtschaftspolitik; Standortwettbewerb; Steuerwettbewerb; Wirtschaftsnahe Infrastruktur; Schätzung; Baden-Württemberg; Deutschland